New tris- and pentakis-fused donors containing extended tetrathiafulvalenes: New positive electrode materials for rechargeable batteries - Iwamoto, Shintaro; Inatomi, Yuu; Ogi, Daisuke; Shibayama, Satoshi; Murakami, Yukiko; Kato, Minami; Takahashi, Kazuyuki; Tanaka, Kazuyoshi; Hojo, Nobuhiko; Misaki, Yohji (Beilstein Journal of Organic Chemistry, 2015)
Derivatives of tris-fused TTF extended with two ethanediylidenes (5), tris- and pentakis-fused TTFs extended with two thiophene-2,5-diylidenes (6–9) were successfully synthesized. Cyclic voltammograms of the tetrakis(n-hexylthio) derivative of 5 and 7 (5d, 7d) consisted of two pairs of two-electron redox waves and two pairs of one-electron redox waves. On the other hand, four pairs of two-electron redox waves and two pairs of one-electron redox waves were observed for the tetrakis(n-hexylthio) derivative of 9 (9d). Coin-type cells using the bis(ethylenedithio) derivatives of 5 (5b), 6 (6b) and the tetrakis(methylthio) derivatives of 5 (5c) and 8 (8c) as positive electrode materials showed initial discharge capacities of 157–190 mAh g−1 and initial energy densities of 535–680 mAh g−1. The discharge capacities after 40 cycles were 64–86% of the initial discharge capacities.
Keywords: cyclic voltammetry; positive electrode materials; rechargeable battery; redox; tetrathiafulvalene

TTF Chemistry–Fundamental and Applications of Tetrathiafulvalene - Yamada, J.; Sugimoto, T. (Kodansha-Springer, 2004)

(untitled) - Canevet, D.; Sallé, M.; Zhang, G.; Zhang, D.; Zhu, D. (Chem. Commun., 2009)

(untitled) - Segura, J. L.; Martín, N. (Angew. Chem., Int. Ed., 2001)

(untitled) - Gorgues, A.; Hudhomme, P.; Sallé, M. (Chem. Rev., 2004)

(untitled) - Misaki, Y. (Sci. Technol. Adv. Mater., 2009)

(untitled) - Misaki, Y.; Matsui, T.; Kawakami, K.; Nishikawa, H.; Yamabe, T.; Shiro, M. (Chem. Lett., 1993)

(untitled) - Iyoda, M.; Hasegawa, M.; Miyake, Y. (Chem. Rev., 2004)

(untitled) - Misaki, Y.; Fujiwara, H.; Yamabe, T.; Mori, T.; Mori, H.; Tanaka, S. (Chem. Lett., 1994)

(untitled) - Nishikawa, H.; Kawauchi, S.; Misaki, Y.; Yamabe, T. (Chem. Lett., 1996)

(untitled) - Misaki, Y.; Kawakami, K.; Higuchi, N.; Nishikawa, H.; Yamabe, T. (Mol. Cryst. Liq. Cryst. Sci. Technol., Sect. A, 1996)

(untitled) - Inatomi, Y.; Hojo, N.; Yamamoto, T.; Watanabe, S.; Misaki, Y. (ChemPlusChem, 2012)

ECS Meeting Abstracts 2008, MA2008-1 - Inatomi, Y.; Hojo, N.; Yamamoto, T.; Shimada, M.; Watanabe, S. (presentation No. 167, 213th ECS meeting, Phoenix, 22.5.2008)

(untitled) - Oyaizu, K.; Suga, T.; Yoshimura, K.; Nishide, H. (Macromolecules, 2008)

(untitled) - Yoshida, Z.; Kawase, T.; Awaji, H.; Sugimoto, I.; Sugimoto, T.; Yoneda, S. (Tetrahedron Lett., 1983)

(untitled) - Sugimoto, T.; Awaji, H.; Sugimoto, I.; Misaki, Y.; Kawase, T.; Yoneda, S.; Yoshida, Z.; Kobayashi, T.; Anzai, H. (Chem. Mater., 1989)

(untitled) - Moore, A. J.; Bryce, M. R.; Ando, D. J.; Hursthouse, M. B. (J. Chem. Soc., Chem. Commun., 1991)

(untitled) - Hansen, T. K.; Lakshmikantham, M. V.; Cava, M. P.; Niziurski-Mann, R. E.; Jensen, F.; Becher, J. (J. Am. Chem. Soc., 1992)

(untitled) - Takahashi, K.; Nihira, T.; Yoshifuji, M.; Tomitani, K. (Bull. Chem. Soc. Jpn., 1993)

(untitled) - Benahmed-Gasmi, A. S.; Frère, P.; Garrigues, B.; Gorgues, A.; Jubault, M.; Carlier, R.; Texier, F. (Tetrahedron Lett., 1992)

(untitled) - Misaki, Y.; Kubo, A.; Matsuda, W.; Fueno, H.; Tanaka, K. (Curr. Appl. Phys., 2006)

(untitled) - Misaki, Y.; Nishikawa, H.; Kawakami, K.; Uehara, T.; Yamabe, T. (Tetrahedron Lett., 1992)

(untitled) - Misaki, Y.; Higuchi, N.; Fujiwara, H.; Yamabe, T.; Mori, T.; Mori, H.; Tanaka, S. (Angew. Chem., Int. Ed. Engl., 1995)

(untitled) - Misaki, Y.; Ohta, T.; Higuchi, N.; Fujiwara, H.; Yamabe, T.; Mori, T.; Mori, H.; Tanaka, S. (J. Mater. Chem., 1995)

(untitled) - Takahashi, K.; Tanioka, H.; Fueno, H.; Misaki, Y.; Tanaka, K. (Chem. Lett., 2002)

(untitled) - Moore, A. J.; Bryce, M. R. (Tetrahedron Lett., 1992)

(untitled) - Nakamura, K.; Shirahata, T.; Miyamoto, H.; Misaki, Y. (Heterocycles, 2011)

Gaussian 09, Revision C.01 (Gaussian, Inc., 2009)

(untitled) - Misaki, Y.; Sasaki, T.; Ohta, T.; Fujiwara, H.; Yamabe, T. (Adv. Mater., 1996)

(untitled) - Aravindan, V.; Gnanaraj, J.; Lee, Y.-S.; Madhavi, S. (J. Mater. Chem. A, 2013)

(untitled) - Thackeray, M. M.; Wolverton, C.; Isaacs, E. D. (Energy Environ. Sci., 2012)

(untitled) - Kato, M.; Ogi, D.; Yao, M.; Misaki, Y. (Chem. Lett., 2013)

(untitled) - Kato, M.; Senoo, K.; Yao, M.; Misaki, Y. (J. Mater. Chem. A, 2014)